Pengungkapan Pengendalian Internal dan Implikasinya terhadap Nilai Perusahaan - Alfita Rakhmayani; Yunita Lisnaningtyas Utami (Jurnal Ekonomika dan Bisnis, 2022)
Internal control is one of the important aspects in presenting reliable information. Transparency through disclosure of internal control systems provides an important role in reducing information asymmetry. This study has a purpose, namely to examine specifically the impact of disclosure of internal control on firm value. The sample of this research is 100 public companies with the largest market cap. Statistical tests were performed using regression analysis. The result is that the disclosure of internal control has a negative impact on firm value.